Os limites da renda como indicador de bem-estar social e desigualdade nos municípios brasileiros - Rodrigo Nunes Ferreira (2017)
This work aims at identifying and exploring measures that allow us to evaluate the social welfare in the Brazilian municipalities during the past two decades, beyond the usual income growth associated metrics. For the empiric approach developed along the three articles composing this thesis, we use various secondary data sources, including the Brazilian demographic censuses of 1991, 2000 and 2010. The data are presented in two different aggregated forms: the division of the country into great regions; and the municipalities grouped by population size. The first part of this thesis consists in a conceptual review, which summarizes elements found in literature about three major themes: social welfare measurement; inequality and development; and the relationship between social welfare and environment. The second part presents the three papers which comprise the thesis. Paper 1 evaluates the social welfare evolution in the Brazilian municipalities in the 1990 and 2000 decades from combining three basic dimensions: income, inequality and infrastructure. Results show that, in spite of a significant income growth, and an improvement in sanitation access in 2000 for a great number of cities in the North and Northeast regions, especially for small municipalities, this increase has not been followed by an improvement in public services infrastructure, nor has it been sufficient to reduce inequality. In Paper 2 we develop a method to evaluate social welfare from an environment point of view. Several nationalrange databases, disaggregated up to the city level have allowed us to design a Municipal Environmental Quality Index - the IQAM. Calculations for the IQAM and its results have outlined the importance of broadening the amount of available information needed to appraise the development stage of Brazilian cities, in order to sharpen the tools for monitoring the social results from public investments. Finally, Paper 3 brings an analysis over the social progress evaluation limits based exclusively on per capita income increase. The social and occupational structure evolution in the 2000 decade, measured from a territorial approach supports the perspective of accessing a new medium class by tracking family earnings patterns. Data presented show an undeniable concentration of real gains from work income for the lower social categories in this decade, and attest that growth income in the 2000 decade was not associated to changes in the pattern of social mobility - ongoing in Brazil since the 1960 decade.